(untitled) (AYUSHDHARA, 2024)
Surgery is the choice of treatment in almost emergency conditions for saving the life of a patient. Sometimes it will leave post operative wound with continuous discharge even with conservative management rarely. Methods: A patient suffering with post operative wound with discharge since 4 yrs. on anterior lateral part of right thigh. Had undergone modern treatment with no results. On consultation, he was advised to apply Kajjalikodaya malahara (KJM) once in a day without any internal medications. Results: The results were appreciable starting from reduction in the discharge to closing the wound cavity without discharge in 60 days. Discussion: The results indicates that the Malahara Kalpana KJM (Kajjalikodaya malahara) therapeutically efficient as indicated in the classics that Asadhya (incurable) Chira varna (chronic wound) will also be relieved.